ANALISA PENGARUH VARIASI KUAT ARUS DAN JARAK PENGELASAN TERHADAP NILAI KEKERASAN SAMBUNGAN LAS BAJA KARBON RENDAH DENGAN ELEKTRODA 6013 METODE ANAVA - Putri, Fenoria (Politeknik Negeri Sriwijaya, Indonesia, 2012)
The process of connecting two or more pieces of metal using electricity as a heat source and the electrode material added as named by the electric arc welding. Welding of the world's most widely used in industry today, this is due to the welding process has advantages when compared with the other connections are: less expensive, the process is relatively faster, lighter, and in more varied engineering and construction. The selection of the current strength and type of electrodes is one of the most important in the welding process, in particular electric arc welding. Materials used in this research process is a low carbon steel and to obtain the optimal results of data processing is done using the method ANAVA. Brinnel hardness testing method aims to determine the hardness of a material. Brinnel intended for testing materials that have hardness Brinnel to 400 HB. Penetration tool used is a hardened steel ball indenter with a diameter of 2.5 mm. From the results of research and testing conducted by using the current 70 A - 110 A with a distance of 1 mm seam and 2 mm, current 110 A with a distance of 1 mm seam which has a high hardness value is 174.5453 BHN. The greater the flow and the larger distance widened welding weldment is happening.